Saluang Mengalun: Estetika Berbicara dalam Perspektif Pendidikan Seni - wijayanto, wasis; Inesya Kalyana Tantri; Aurelia Cahya Fadhilatul Khalila (Program Studi Etnomusikologi, Fakultas Ilmu Budaya, Universitas Mulawarman, 2025)
This study examines the aesthetic values ​​in the traditional wind instrument Saluang from Sumatra, which is an integral part of the cultural identity of the Minangkabau people. The background of this study focuses on the decline in appreciation of traditional music among the younger generation, as well as the importance of preserving Saluang as a cultural heritage. The method used is descriptive qualitative with ethnographic research type, analyzing various sources such as scientific journals, books, and online articles. The results of the study show that Saluang has rich aesthetic values, reflected in its simple physical form, made of bamboo, and playing techniques that produce soft and melodious sounds. Saluang performances are often accompanied by poems that are full of philosophical meaning, adding a deep aesthetic dimension. The discussion highlights the interaction between visual form, playing techniques, and socio-cultural contexts that create a unique aesthetic experience. In conclusion, Saluang is not just a musical instrument but also a representation of the aesthetic and philosophical values ​​of the Sumatran people, which need to be preserved to maintain cultural identity and increase the younger generation's appreciation of this heritage.